Implementasi Program Penanggulangan Kemiskinan Di Jawa Tengah - Zuhri, Mursid; Sofianto, Arif (Jurnal Penelitian Kesejahteraan Sosial, 2020)
Central Java is one of the centers of national economic growth, but poverty still requires special attention. The purpose of this study is to describe the implementation of poverty alleviation programs in Central Java, as well as formulate an implementation of poverty reduction designs that are in accordance with the needs in Central Java. This type of research is descriptive, using a mixed method approach, namely qualitative and quantitative. The location of this study was in 15 districts in Central Java with the highest poverty rate, with 777 people involved, from the poor, community / institutional leaders, village officials, and program assistants. Data collection techniques used were interviews, observation, and Focus Group Discussion (FGD). Qualitative data analysis using an interactive model developed by Miles and Huberman. Quantitative data analysis is by descriptive statistics in the form of averages and percentages. The conclusion of this research is "First, the implementation of poverty alleviation programs many cases are misplaced due to inaccurate data, more of a giving nature which increases consumerism rather than productive, there is no education to the community to escape poverty. Secondly, the expected design of poverty reduction is to use the principle of empowerment, the main role being in the poor where they participate in determining the program to be run, with the principle of educating the poor to be productive and independent.